‘‘Scalar Wave Effects according to Tesla’’[3] and ‘‘Far Range Transponder’’[4] by K. Meyl - KUHLKE, DIETRICH (Journal of Scientific Exploration, 2010)
In the recent past a hypothetical waveform, longitudinal electric or magnetic waves, shortly denoted electric scalar waves or simply scalar waves, is discussed. To give a theoretical proof of the existence of such longitudinal electric waves K. Meyl starts with an approach that he calls a ‘‘new and dual field approach’’(3,4) and that should be more general than Maxwell’s equations. In the following commentary we discuss the cogency of the theoretical considerations presented in Meyl’s two articles(3,4) in order to answer the question of whether this approach really gives an indication of the existence of longitudinal electric waves. It is shown that this ‘‘new and dual field approach’’ actually consists of the very special relations describing plane transverse electromagnetic waves. The ‘‘Fundamental Field Equation’’ presented in Meyl’s articles also does not have any solution in the form of longitudinal electric waves. A general weakness of the two articles is that Meyl does not present any solutions or a clue related to possible solutions of the partial differential equations he presents. Thus, for example, the discussion following the ‘‘Fundamental Field Equation’’ (key words: A possible world equation, quantization of the field) lacks any foundation. The model Meyl starts from describes the propagation of electromagnetic fields through media with special properties and does not include any sources responsible for the emission of electromagnetic radiation. Hence, the equations he obtained do not describe the near field behavior of electromagnetic waves. The consequence is that the properties he ascribed to the near field are also without any foundation. Keywords: Near field as a vortex field—vortex model of the scalar waves— phenomenology—antenna noise caused by Lorentz contraction of vortices and vortex works as a frequency converter